Analisis Pengaruh Pemahaman Etika Pajak terhadap Kepatuhan Pajak - Anton, Anton; Aditya, Adbeel (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
Taxes have a very important role for the state, because all expenditures used for development come from taxes. In this case, psychological factors that affect tax compliance are needed, namely ethical factors. This study was conducted with the aim of empirically testing and analyzing the effect of understanding tax ethics on increasing tax compliance. The population used in this study were students from FEB and non-FEB at AKI Semarang University who had received taxation courses and had never received taxation courses with a sample of 30 people using the non-probability method. Data collection techniques using a questionnaire. Data analysis using SPSS 23. The results of the analysis using the experimental method obtained a significance value of t (t test) for the variable understanding of tax ethics of 0.032 whose value is <0.05 with a positive t count of 2.258. It states that tax ethics has a positive and significant effect on tax compliance.